Analysis of risk management practices in European countries - Zhang, Wei (2019)
Banking industry differs from other industries and generates unique risk management challenges. There is no denying the fact that risk management practices of banks have a significant influence on banks’ performance and default risks. Well governed banks have been noted to have higher performance. Though corporate governance is multi-dimensional, this study examined the impact of the presence of Chief Risk Officer (CRO), the risk committee and Chief Executive Officer(CEO) and Chairman duality on the performance measures, namely, return on equity (ROE) and risk measures namely non-performing loans (NPLs) of European private and quoted banks covering the period 2009 to 2018. These variables were used, and analysed within the framework of panel data methodology. Though, limited evidence on the relationship between risk governance variables, banks’ performance, and risk measures was available, banks in Europe should continue to improve risk management and should be encouraged to establish a CRO, risk committee and separation of CEO and Chairman for effective performance and risk control should, keeping in view the bank’s individual circumstances and the scale of growth